2011
DOI: 10.4319/lom.2011.9.245
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring methane oxidation rates using lowlevels of 14C‐labeled methane and accelerator mass spectrometry

Abstract: We report a new method for methane oxidation rate measurements that uses 10 3 -10 5 times less 14 C-CH 4 than existing measurements by taking advantage of the high sensitivity of accelerator mass spectrometry. Methane oxidation in the marine environment is a microbial process of global importance because it prevents methane released from underlying reservoirs from reaching the ocean and atmosphere. Rate measurements provide a crucial tool for assessing the efficacy of this process across a range of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 45 publications
2
59
1
Order By: Relevance
“…These authors (Reeburgh et al 1991) conclude that the observed variability may be attributed to changes in the water mass sampled as gyres drive lateral mixing over short time scales. The difference between the rates observed in Ward's study and in the current study may also be due to natural variability in the upper water column of the SMB, but the discrepancy highlights the need for additional intercomparison of available techniques, as conducted by Pack et al (2011) for the low-level 14C, accelerator mass spectrometry based technique. The combined observations of long turnover times in Ward's study and long turnover times associated with the 2007 sub-surface methane maxima (25-50 m) in this study (Fig.…”
Section: Results and Discussion Methanotrophic Potentialcontrasting
confidence: 80%
See 1 more Smart Citation
“…These authors (Reeburgh et al 1991) conclude that the observed variability may be attributed to changes in the water mass sampled as gyres drive lateral mixing over short time scales. The difference between the rates observed in Ward's study and in the current study may also be due to natural variability in the upper water column of the SMB, but the discrepancy highlights the need for additional intercomparison of available techniques, as conducted by Pack et al (2011) for the low-level 14C, accelerator mass spectrometry based technique. The combined observations of long turnover times in Ward's study and long turnover times associated with the 2007 sub-surface methane maxima (25-50 m) in this study (Fig.…”
Section: Results and Discussion Methanotrophic Potentialcontrasting
confidence: 80%
“…Methanotrophic potential was studied in sites throughout the Southern California Borderland at sites described in , Mau et al, 2011, Pack et al, 2011and Heintz et al, 2012. The relationship between oxidation rate and environmental conditions was investigated to understand controls on methanotrophy and to develop methane budgets valid at local and basin scale.…”
Section: Results and Discussion Methanotrophic Potentialmentioning
confidence: 99%
“…MOX can be measured by the decrease of methane concentration over time (Scranton and Brewer 1978;Abril et al 2007), the change in isotopic composition (Bastviken et al 2002) or by a combination of stable isotope and conservative tracer measurements (Rehder et al 1999;Heeschen et al 2004). However, adding a radioactive tracer such as 3 H-CH 4 (Valentine et al 2001;Mau et al 2013) or 14 C-CH 4 (Reeburgh et al 1992;Pack et al 2011) makes quantification more sensitive. Especially the method using 3 H-CH 4 has become more and more established over the last decade as sample processing requires only a few steps, which can be carried out on board a research vessel, the tracer has become commercially available, and it has several advantages compared to 14 C-CH 4 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This significantly alters the concentration of the gas especially in samples collected from environments with low in situ methane concentrations. However, recently also a low-level 14 C-CH 4 method has been proposed, where 14 C is measured with accelerator mass spectrometry (Pack et al 2011 Regardless of the radiotracer, more and more often tracer incubations are conducted on board of research vessels, where similar to any laboratory country specific radiation regulations apply. The transport of the radioactive tracer, radioactive samples, and radioactive waste has to be organized according to these safety regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the size of the stripping probe itself (McNichol et al 1994) is optimized for water samples of about 250 mL, which limits the application of the conventional method in small water samples such as pore water. Pack et al (2011) developed a compact stripping probe with good efficiency (99.1 ± 2.2%, n = 8) that requires only 60 mL water, but the extraction procedure still involves cleaning and flushing between samples, that limits sample processing throughput.…”
mentioning
confidence: 99%